Stereoselective synthesis of epoxyisoprostanes: an organocatalytic and "pot-economy" approach1. Issue 50 (25th June 2015) - Weng, Jiang; Wang, Sheng; Huang, Lin-Jie; Luo, Zhang-Yi; Lu, Gui
<x xml:space="preserve">Abstract</x> An efficient and direct synthetic route to epoxyisoprostane EC methyl ester has been accomplished in 8 steps (10% overall yield) from readily available starting materials using a series of asymmetric organocatalytic reactions and one-pot operations.